The role of strategic awareness in high performance : analytical research at the Higher Institute for Security and Administrative Development / Ministry of Interior (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to determine the level at which strategic awareness (the independent variable) with its dimensions (internal strategic awareness, external strategic awareness, current strategic awareness, future strategic awareness) can contribute to enhancing high performance (the dependent variable) with its dimensions (continuous improvement and renewal, quality of management, employee quality, long-term orientation, openness, and work orientation) at the Higher Institute for Security and Administrative Development / Ministry of Interior, relying on the descriptive and analytical approach. (107) individuals represented the research population, and the research sample was (84) from the institute's upper, middle, and lower administrative levels. The sample was chosen at random (relatively) stratified from (the general manager, his assistants, department managers, and division managers), and then (80) were retrieved from them. The one suitable for statistical analysis was (78). The research adopted the questionnaire as the primary tool for collecting data. Its first part was devoted to the independent variable, strategic awareness, which included 20 items. As for the second (dependent) variable, high performance, it was measured through 25 items, making a total of 45 items, in addition to supplementing it with personal interviews as an auxiliary tool for collecting data and surveying the opinions of the sample. The research adopted several statistical methods to process the data, including the arithmetic mean, standard deviation, coefficient of variation, relative importance, Crum-Bach alpha coefficient, Pearson correlation coefficient, and simple linear regression, while the research relied on the statistical analysis of the data on programs (SPSS V28). The most prominent results of the research were embodied in the presence of strategic awareness, which significantly strengthened the high performance of the Higher Institute for Security and Administrative Development.